Imaging Spontaneous Neuronal Activity with Voltage‐Sensitive Dyes. Issue 3 (24th March 2021) - Raliski, Benjamin K.; Kirk, Molly J.; Miller, Evan W.
Abstract: Accurately mapping changes in cellular membrane potential across large groups of neurons is crucial for understanding the organization and maintenance of neural circuits. Measuring cellular voltage changes by optical means allows greater spatial resolution than traditional electrophysiology methods and is adaptable to high‐throughput imaging experiments. VoltageFluors, a class of voltage‐sensitive dyes, have recently been used to optically study the spontaneous activity of many neurons simultaneously in dissociated culture. VoltageFluors are particularly useful for experiments investigating differences in excitability and connectivity between neurons at different stages of development and in different disease models. The protocols in this article describe general procedures for preparing dissociated cultures, imaging spontaneous activity in dissociated cultures with VoltageFluors, and analyzing optical spontaneous activity data. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Preparation of dissociated rat hippocampal or cortical cultures Alternate Protocol : Preparation of microisland dissociated cultures Basic Protocol 2 : Imaging of spontaneous activity in dissociated cultures using voltage‐sensitive dyes Basic Protocol 3 : Analysis of spontaneous activity imaging data